A Critical Analysis of Islamic Law and Fatwa of MUI (Majlies Ulama Indonesia) & NU (Nahdlatul Ulama’) on A Gold-Backed Cryptocurrency (OneGram) - M. Asrorun Niam Sholeh; Muhammad Fauzinudin Faiz; Moh. Muhlis Anwar (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
Cryptocurrency is a result of recent development of digitalization in the financial transaction. OneGram is a part of it that uses gold instruments to back up and maintain its value stable. The purpose of this study is to explore how Islamic law and MUI & NU, through their fatwa, percieve the OneGram. This research uses a qualitative approach to gain a deep understanding of the OneGram by using secondary data collected from the Quran, hadith, relevant academic journals according to Islamic law and fatwas from both organization. The results of this study state that OneGram is allowed by Islamic law and the fatwa to be used as digital payment system. OneGram is furthermore supervised by shariah supervisory board to avoid gharar (uncertainty) and maysir (gambling) in maintaining its value. The unique fact from this digital currency is that the use of gold in transaction had been applied in the time of Prophet Muhammad SAW. From this digital development, OneGram as a gold-backed cryptocurrency can revive the function of dinar as currency. OneGram transforms the gold value in dinar coin which physically has no flexibility in today transaction to the gold value in digital platform which has flexibility in digital transaction with broad accesability.